Protective effects of melatonin solid lipid nanoparticles on testis histology after testicular trauma in rats - Mehri Mirhoseini; Zahra Rezanejad Gatabi; Majid Saeedi; Katayoun Morteza-Semnani; Fereshteh Talebpour Amiri; Hamid Reza Kelidari; Abbas Ali Karimpour Malekshah (Wolters Kluwer Medknow Publications, 2019)
Testicular traumatic injuries occur frequently, which can result in an alteration in spermatogenesis. These injuries can also cause oxidative stress and male infertility. Antioxidant efficiency of melatonin (MLT), known as a potent antioxidant, will be improved if used in a form of solid lipid nanoparticles (MLT-SLN). The aim of the current study is to evaluate the effect of MLT-loaded SLN on traumatic testis in rats. In this study 32 adult male Wistar rats were divided into 4 groups. Group 1 (sham group), right testicle was drawn out from the scrotum and returned without manipulation. Group 2, right testicle was dropped by 25 g sinker for 4 times. Group 3, animals were received a single dose (25 mg/kg) of MLT intraperitoneally after trauma. Group 4, animals were received a single dose of MLT-SLN intraperitoneally after trauma. Under anaesthesia, rats were sacrificed, and their testicles were removed three days after the surgery. After tissue processing, the sample sections were H&E stained. MLT and MLT-SLN could partially repair spermatogenesis by Johnson's criteria but the repairs were significant only in MLT-SLN group (P = 0.02). Trauma decreased seminiferous tubule diameter and its epithelium height. MLT could restore epithelium height (P ≤ 0.05) but its NPs improved both epithelium diameter (P ≤ 0.05) and thickness (P ≤ 0.001). The Malondialdehyde increased significantly in trauma group (P = 0.002), but decreased in MLT and NPs groups compared to trauma group (P = 0.098 and P = 0.002 respectively). This decrease was significant only in NPs group. Testicular trauma disturbed spermatogenesis, morphometric, and oxidative parameters. MLT and specially MLT-SLN improved traumatic damages.